Exploring trends and challenge on second language learning using bibliometric analysis - Prihatini, Arti; Pangesti, Fida; Zamahsari, Gamal Kusuma (Diksi, 2025)
Second language learning is becoming a research trend. Unfortunately, there was a lack of research that sketched this field. In filling this gap, this study aims to map the research trends in second language learning in Scopus. This study was conducted by bibliometric analysis involving research articles on second language learning in 2013-2022. The data were collected from Scopus. The data were analyzed using the VOSviewer application to visualize research trends. The current study found that research clusters focused on students (motivation and emotions), second language learning, and linguistics elements (word, lexicon, and speech). Research focuses on school-based second language learning. Over the past decade, second language learning has combined education, psychology, neurology, and technology. From 2017, second language learning publications rose considerably. The United States has published the most second-language acquisition articles over the past decade. The United Kingdom is the second country with the most publications. Five of the ten top countries originate from the Europe, two from North America, and the remaining two from China and Hong Kong. The results benefit teachers in teaching, students in the learning process, and researchers in investigating second language learning.